The Influence Of Shopee Live Advertising And Product Quality On Interest In Buying Clothing Products In Shopee E-Commerce - Nunuk Indarti; Aida Fitriyah; Nurus Sobakh (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine the effect of shop live advertising and product quality partially or simultaneously on the buying interest of Economic Education Students at PGRI Wiranegara University. This research begins with the number of teenagers who are easily influenced by live shop advertisements and product quality in buying clothes, especially in shop e-commerce. The population in this study were students of economic education at PGRI Wiranegara University, with a sample of 70 students who used the shop application. The data collection technique used a questionnaire that was tested for validity and reliability. The data analysis technique used multiple linear regression, classical assumption test, T-test, F test, and coefficient of determination. The results of this study indicate that live shop advertising has a positive and significant effect on buying interest in clothing products for Economic Education Students at PGRI Wiranegara University; product quality partially has a positive and significant effect on buying interest in clothing products for Economic Education students at PGRI Wiranegara University. Shopee live advertising and product quality simultaneously have a positive and significant effect on buying interest in clothing products for Economic Education Students at PGRI Wiranegara University. The conclusion of this study is that the correlation coefficient value shows that 61.1% of the buying interest variable can be explained by the shop's live advertising variables and product quality. In comparison, the remaining 38.9% is explained by other variables that were not examined in this study.